HUTAN SEBAGAI GUDANG KEANEKARAGAMAN PLASMA NUTFAH - Triwanto, Joko (Jurnal Bestari, 2001)
continuous development "must improve on these concentrations; to realize the conservation and function of germ-plasm, rehabilitate the environmental flaw, and increase the quality of milieu. The milieu improvement is the important part of ecosystem used to be the life buffer of animate culture. Thus, the society awareness is needed to know what the important influence of germ-plasm to its life. Moreover, providing information and education both formal and non-formal, and giving the stimulus of law